Outcomes of uninsured midwifery clients in Ontario, Canada: A retrospective cohort study. (October 2019) - Darling, Elizabeth Kathleen; Bennett, Nicole; Burton, Nadya; Marquez, Olivia
Abstract: Objective: To describe the characteristics, health service utilization, and clinical outcomes of Ontario residents who are not covered by the Ontario Health Insurance Plan and receive services from Ontario midwives. Design: Retrospective cohort study. Setting: Ontario, Canada. Participants: All midwifery courses of care resulting in births between April 1, 2012 to March 31, 2015 and captured in the BORN perinatal registry. Within this cohort we compared midwifery clients without publicly funded health insurance to those covered by the Ontario Health Insurance Plan (OHIP). Measurements and findings: Of 55, 634 midwifery clients assessed in Ontario, 92.8% were insured by OHIP and 7.2% were not insured. Among uninsured clients, 66.3% attended a prenatal visit during the first trimester compared to 92.8% of insured women, with uninsured clients presenting with fewer pre-existing conditions. A higher proportion of uninsured clients (33.9%) planned to birth at home and 28.7% of clients' actual place birth was in the home, compared to 19.6% and 16.6% of insured clients respectively. Rates of both spontaneous labour and spontaneous vaginal birth were higher among uninsured clients (82.1% and 81.1%, respectively), compared to insured clients (77.3% and 78.1%, respectively). Clinical outcomes were generally similar, with postpartum hemorrhage (3.4%), preterm birth (5%), and small-for-gestational age (2.1%) slightly more common among uninsured clients compared to insured clients (2.9%, 4.4%, and 1.7%, respectively). Rates of most complications were lower for uninsured clients. Key conclusions: Overall, uninsured clients used less services compared to insured clients and had good clinical outcomes under midwifery care in Ontario. Findings of this study support the policy decision in Ontario to fund midwifery care for uninsured clients and suggest that uninsured clients are well suited for midwifery care. Implications for practice: Funding midwives to serve uninsured clients is appropriate and may improve uninsured clients access to care.